Evaluation of Sand Constitutive Models for Analysis of Piled Raft Foundation - Hassan O. Abbase (Diyala Journal of Engineering Sciences, 2018)
Constitutive models play an important origin in the geotechnical problems design. In order to make the models useful to geotechnical engineers, some numerical predictions are presented to compare the performance of different models with experimental results (Full scale tests). It was found from this study that hardening soil model (HS small model) gave good prediction of settlement more than hardening model and Mohr-Coulomb model. Also, the errors in prediction of maximum settlement pile raft, pile group and raft are ranged (3-4) %, (6-7) % and (27-36) % for hardening soil with small strain model, hardening model and Mohr-Coulomb model respectively